2023
DOI: 10.1111/jiec.13374
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic rarity of electrical and electronic waste: Assessment and policy implications for critical materials

Abstract: The strategic relevance of extracting raw materials from waste from electrical and electronic equipment (WEEE) in the EU is increasing due to value chain risks caused by geopolitical instability, accessibility of specific minerals, and decreasing reserves due to growing extraction rates. This article examines the quantities of so‐called critical raw materials (CRMs) originating within WEEE streams from a depletion perspective. Presently, current recycling targets are based solely on mass collection and recycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It can therefore be concluded that it is necessary to "move mountains" in order to extract the ore. In this sense, paradigms have to change, since higher quantities of materials can be extracted from a landfill than from the primary source (mine) [20]. The EU (European Union) had an average increase of 50% in raw materials, particularly ferrous materials, a fact that is directly related to the war in Ukraine, creating real chaos in manufacturing industries and throughout the SCM.…”
Section: The Sense Of Green Logistics On the Times Of Warmentioning
confidence: 99%
“…It can therefore be concluded that it is necessary to "move mountains" in order to extract the ore. In this sense, paradigms have to change, since higher quantities of materials can be extracted from a landfill than from the primary source (mine) [20]. The EU (European Union) had an average increase of 50% in raw materials, particularly ferrous materials, a fact that is directly related to the war in Ukraine, creating real chaos in manufacturing industries and throughout the SCM.…”
Section: The Sense Of Green Logistics On the Times Of Warmentioning
confidence: 99%
“…The literature also criticized the references of the existing targets: in general for being mass-based, therewith neglecting the (ecological) value and scarcity of materials in EEE [69,97], and specifically the 65% collection target because its 'Put on Market' reference does not properly reflect the amount of WEEE that is generated or available for collection [74]. One waste treatment operator acknowledged that the recycling of CRMs makes no difference if targets remain weight-related, given their low weight share.…”
Section: Eu Waste Legislationmentioning
confidence: 99%
“…To solve the issues regarding the targets in the WEEE Directive, it has been suggested to set more stringent targets [98], introduce new targets, such as for reuse and preparation for reuse [6,99], or introduce qualitative targets, focusing on certain materials or the quality of collected products [97,100,101]. According to two interviewees, such targets are possible, but do require that the need for achieving such targets is already taken into account at the product stage.…”
Section: Eu Waste Legislationmentioning
confidence: 99%
“…Lepawsky et al (2017) call for electronics repair, reuse, repurposing and recycling with ethical and sustainable considerations. Various EPR versions make producers and importers responsible for e‐waste recycling and have been studied or proposed as domestic solutions (Atasu & Subramanian, 2012; Campbell‐Johnston et al, 2021; Campbell‐Johnston et al, 2022; Lin et al, 2001; Schnoor, 2012; Thapa et al, 2022; Widmer et al, 2005). In the EU's WEEE directive, EPR guides e‐waste management and Nigeria aspires to establish one.…”
Section: Theoretical Context: Circularity and Just Transitionmentioning
confidence: 99%